Teachers and Parents’ Views on the Holistic Development of Preschoolers in Islamabad, Pakistan - Yunus, Saima; Khan, Fahad Munir; Khan, Abdul Ahad Munir; Khan, Maaz Munir; Khan, Abdur Rafay Munir (2025)
This study examines the concept and practice of early childhood education (ECE) in a rural setting in Islamabad in Pakistan. The research takes into consideration various aspects that influence the development of children, including; their previous experience in learning programs, awareness of parents about education programs, and the impact of social and political conditions. It is primarily concerned with language, thinking, and social development of children. The participants were 25 in number and were recruited on verbal consent. The results indicate that social and political situations, and low knowledge of holistic development only have minor influence on the actual development of children. ECE, which works with children aged between eight andbirth years old, also helps the kids to be ready to join school by enhancing their emotional, physical, social, and intellectual development. Another area addressed by the research is the influence of school curriculum, teaching materials, and the role played by parents in influencing the learning of the children. The study, undertaken under the Federal Directorate of Education in Islamabad, employed interviews, surveys and classroom observations with teachers, parents and school officials. The findings illustrate why policymakers must come up with early education initiatives that would be responsive to local cultures, social, and economic realities. Policy modification to suit the local requirements can enhance access, quality and overall development of children in rural Islamabad.